Limited memory solution of bound constrained convex quadratic problems arising in video games - Ferris, M; Wathen, A; Armand, P (2007)
We describe the solution of a bound constrained convex quadratic problem with limited memory resources. The problem arises from physical simulations occurring within video games. The motivating problem is outlined, along with a simple interior point approach for its solution. Various linear algebra issues arising in the implementation are explored, including preconditioning, ordering and a number of ways of solving an equivalent augmented system. Alternative approaches are briefly surveyed, and some recommendations for solving these types of problems are given. © EDP Sciences, ROADEF, SMAI 2007.